2022
DOI: 10.1021/acsmacrolett.2c00053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Micellization of Bottlebrush Poloxamers

Abstract: Bottlebrush polymers are characterized by an expansive parameter space, including graft length and spacing along the backbone, and these features impact various structural and physical properties such as molecular diffusion and bulk viscosity. In this work, we report a synthetic strategy for making grafted block polymers with poly­(propylene oxide) and poly­(ethylene oxide) side chains, bottlebrush analogues of poloxamers. Combined anionic and sequential ring-opening metathesis polymerization yielded low dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Fitting the decay curve to the biexponential model indicated that the sizes of the populations differ by a factor of 2, which is attributed to a coexistence of free chains ( R h,free chains = 3.9 ± 0.5 nm) and micelles ( R h,micelles = 8.0 ± 1.5 nm). Because bottlebrush molecules adopt extended conformations, micelles are expected to be roughly twice as large as free chains ( R h,micelle ∼ 2 R h,free chain ) …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fitting the decay curve to the biexponential model indicated that the sizes of the populations differ by a factor of 2, which is attributed to a coexistence of free chains ( R h,free chains = 3.9 ± 0.5 nm) and micelles ( R h,micelles = 8.0 ± 1.5 nm). Because bottlebrush molecules adopt extended conformations, micelles are expected to be roughly twice as large as free chains ( R h,micelle ∼ 2 R h,free chain ) …”
Section: Resultsmentioning
confidence: 99%
“…Based on the side-chain lengths and grafting density, we expect the BBPs are loose brushes, so the side chains are Gaussian coils while the backbone is extended . Prior work has shown that the core dimensions of BBP micelles reflect the behavior of a wormlike chain with a persistence length of ∼10 nm, which is significantly higher than the 0.7 nm persistence length of linear polynorbornene …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations